The Effect of Dual Role Conflict and Job Stress on the Performance of Female Employees at the Pekanbaru City Health Office - Sinulingga, Andini Putri; Hasyim, Hariza (MUI Kota Pekanbaru, 2024)
The Purpose of this study was to determine the effect of Dual Role Conflict and Job Stress on the Performance of Female Employees at the Pekanbaru City Health Office. With data analysis in this study is quantitative using multiple linear regression methods and the data is analyzed using the SPSS program. Based on the results of this research, it shows that dual role conflict has no effect on the performance of female employees at the Pekanbaru City Health Office. Meanwhile, the work stress variable affects the performance of female employees at the Pekanbaru City Health Office. Simultaneously, the dual role conflict and work stress variables have a significant effect on the performance variables of female employees at the Pekanbaru City Health Office. The R Square value of 0.300 or 30% means that the female employee performance variable is influenced by dual role conflict and work stress while the remaining 70% is influenced by other variables not used in this study.